Vers une intégration de modèles de l’intervention enseignante dans le jeu des enfants à l’éducation préscolaire - Allard, Edith; Bouchard, Caroline; Richard, Vincent (Canadian Journal of Education/Revue canadienne de l'éducation, 2024)
This theoretical article aims to clarify the conceptualization of teachers’ interventions in children’s play in preschool. From the presentation and analysis of scientific literature and models on teachers’ intervention in play, three dimensions were identified: types of intervention made by the teachers, the roles adopted by them, and the nature of the learning. These dimensions were then used to analyze four models of teachers’ intervention in play, in addition to considering the person who controls the play between the adult and the child. By weaving links between these dimensions and models, three forms of teachers’ interventions are identified and presented in an integrative theorical proposal: (1) open free play, (2) guided free play, and (3) directed “play.” Each of these forms of teachers’ interventions is clarified by emphasizing what characterizes and distinguishes them, which, according to us, might facilitate the interpretation of studies’ results by introducing a common framework for comparing them. Likewise, this proposal leads preschool teachers to better situate and understand their interventions in play context.